Surrazionalismo: Bachelard e la plasticità della ragione (Altre Modernità, 2012)
With his article Surrationalism, 1936, (now in The Rationalist Engagement), Gaston Bachelard codifies the neologism ‘surrationalism’ by which he describes his engagement in favor of a kind of rationality that rejects any closing within the dogmas of indisputable knowledge. The aim of this paper is not only to analyze this concept in its connection with the ‘philosophy of no’ and the ‘philosophy of re’, but also to highlight the semantic effect of the ‘sur’ that in Bachelard’s text multiplies and produces many neologisms. This necessity to provoke language to take over the effect of liberty produced by surrationalism could find another theoretical resource in the term ‘plasticity’, as it is used by Catherine Malabou to characterize Hegelian thought and as it is taken by Derrida to identify a kind of reason which does not dominate reality.